Association of sulfur dioxide exposure with circulatory system deaths in a medium-sized city in Brazil - Amancio,C.T. (2012)
There is a demonstrable association between exposure to air pollutants and deaths due to cardiovascular diseases. The objective of this study was to estimate the effects of exposure to sulfur dioxide on mortality due to circulatory diseases in individuals 50 years of age or older residing in São José dos Campos, SP. This was a time-series ecological study for the years 2003 to 2007 using information on deaths due to circulatory disease obtained from Datasus reports. Data on daily levels of pollutants, particulate matter, sulfur dioxide (SO2), ozone, temperature, and humidity were obtained from the São Paulo State Environmental Agency. Moving average models for 2 to 7 days were calculated by Poisson regression using the R software. Exposure to SO2 was analyzed using a unipollutant, bipollutant or multipollutant model adjusted for mean temperature and humidity. The relative risks with 95%CI were obtained and the percent decrease in risk was calculated. There were 1928 deaths with a daily mean (± SD) of 1.05 ± 1.03 (range: 0-6). Exposure to SO2 was significantly associated with mortality due to circulatory disease: RR = 1.04 (95%CI = 1.01 to 1.06) in the 7-day moving average, after adjusting for ozone. There was an 8.5% decrease in risk in the multipollutant model, proportional to a decrease of SO2 concentrations. The results of this study suggest that residents of medium-sized Brazilian cities with characteristics similar to those of São José dos Campos probably have health problems due to exposure to air pollutants.